Peran Mediasi Minat Beli Pada Pengaruh Kepercayaan Merk Terhadap Keputusan Beli (Studi Pada Fakultas Teknik Universitas Muhammadiyah Tangerang) - Lutfi Lutfi; Hayati Nupus (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to analyze the mediating effect of purchase intentions on the influence of brand trust on purchase decisions, studies at the Faculty of Engineering, University of Muhammadiyah Tangerang (FT-UMT). The sampling technique in this study with nonprobability sampling technique, whereas in determining the sample using accidental sampling technique. The population is all FT-UMT students with a total of 1817 students. The sample of respondents who will be analyzed in this study is 100 respondents. The findings of this study are the mediating effects of Purchase Intentions on Brand Trust Influence on Purchase Decisions. Future research is expected to examine the further effects of Purchase Decisions on Marketing Performance. The final part of this paper also discusses the implications of this study.